2008
DOI: 10.1021/cm7033917
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Thermal Properties, Electrical Conductivity, and Crystal Structure in the BaCe0.80Y0.20O2.9 Proton Conductor

Abstract: In this paper we report an extensive neutron diffraction investigation at high temperature on the BaCe 0.80 Y 0.20 O 2.9 proton conducting material. Our results precisely define the structural evolution of the compound as a function of temperature which is from a monoclinic (room temperature) to a cubic (800°C) structure. Neutron data have been correlated to calorimetric measurements (TGA and DSC) and conductivity properties of the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
6
53
0
Order By: Relevance
“…This discontinuity in thermal expansion and proton diffusion has been observed for the same or for similar materials41424344. Literally, the thermal expansion coefficient decreases in the temperature range where we observe the onset of considerable proton diffusivity and conductivity, that is, here in the range 650–700 K. Most noteworthily, the jump time τ is correctly predicted for the Ce–O stretching mode by the proton polaron model (equation (7)), whereas the O–H stretching is validated only for T >700 K.…”
Section: Resultssupporting
confidence: 69%
“…This discontinuity in thermal expansion and proton diffusion has been observed for the same or for similar materials41424344. Literally, the thermal expansion coefficient decreases in the temperature range where we observe the onset of considerable proton diffusivity and conductivity, that is, here in the range 650–700 K. Most noteworthily, the jump time τ is correctly predicted for the Ce–O stretching mode by the proton polaron model (equation (7)), whereas the O–H stretching is validated only for T >700 K.…”
Section: Resultssupporting
confidence: 69%
“…For BCY20 rich structural phase transformations as a function of temperature and water uptake were found to occur by structure sensitive techniques [12][13][14][15][16][17][18]. The oxides BaCe1−xYxO3−δ with lower substitution rate (x≤0.15) feature seemingly a higher structural stability [13,14,16].…”
Section: Bace1−xyxo3−δ In Sofcsmentioning
confidence: 99%
“…The oxides BaCe1−xYxO3−δ with lower substitution rate (x≤0.15) feature seemingly a higher structural stability [13,14,16]. Nevertheless, the crystalline structures even at ambient temperature remain questioned because depending on synthesis and processing conditions subtle local tilting and distortion of the Ce/Y containing oxygen octahedra results in various structures of monoclinic, rhombohedral and orthorhombic symmetry [12,18].…”
Section: Bace1−xyxo3−δ In Sofcsmentioning
confidence: 99%
“…However, we regard that the sensitivity and resolution of their observed X-ray diffraction patterns were so low that accurate crystal structure could not be analyzed in their study. Malavasi and coworkers 20) 19) and carried out neutron diffraction measurement with high resolution. They reported that the crystal system of BaCe 0.8 Y 0.2 O 3¹¤ was monoclinic distorted perovskite although it contained 7 mol % of orthorhombic phase as impurities.…”
Section: Introductionmentioning
confidence: 99%